Chalcogenide‐Based Narrowband Photodetectors for Imaging and Light Communication. (29th December 2022) - Xu, Yalun; Li, Ruiming; Bai, Songxue; Li, Yanyan; Jia, Zhenglin; Yang, Yujie; Cui, Enkang; Yao, Fang; Wang, Du; Lei, Cheng; Lin, Qianqian
Abstract: Chalcogenide‐based semiconductors have recently emerged as promising candidates for optoelectronic applications, mainly benefiting from their facile and low‐cost processability, chemical versatility, and tunable optoelectronic properties. Despite the recent success of chalcogenide‐based thin‐film photovoltaics, they have been barely leveraged in photodetection, mainly due to the complicated charge transport related to the trap states. In addition, most of the chalcogenide photodetectors are reported for broadband, visible photodetection, which is facile but lacks of impact for real applications. However, it is also possible to modulate the charge carrier dynamics of chalcogenide‐based materials, and devise novel devices, which can possess extra compelling features. These possibilities provide strong incentives for a detailed study on the chalcogenides‐based narrowband photodetectors, which are achieved by a filterless, charge collection narrowing strategy. The optimized narrowband photodetectors also exhibit extremely fast‐response (≈240 ns), relatively low dark current and noise, large linear dynamic range, and most importantly tunable spectral discrimination covering the whole range from UV to NIR. These devices also demonstrate great potential for imaging and communication. Abstract : Chalcogenide‐based narrowband photodetectors are achieved via a filterless and charge collection narrowing strategy. Charge carrier dynamics of chalcogenide‐based materials are systematically investigated, and tunable spectral discrimination covering the whole range from UV to NIR has been demonstrated with fast‐response (≈240 ns), which is promising for imaging and communication.